Nanoparticle sensor for label free detection of swine DNA in mixed biological samples - Ali, M.E; Uda, Hashim, Prof. Dr.; S., Mustafa; Y. B., Che Man; M. H. M., Yusop; Mohd Fazlul, Bari, Dr.; Kh. N., Islam; M. F., Hasan (IOP Publishing Ltd, 2011)
Link to publisher's homepage at http://iopscience.iop.org/